Boosting thermoelectric performance of n-type PbS through synergistically integrating In resonant level and Cu dynamic doping. (January 2021) - Hou, Zhenghao; Wang, Dongyang; Hong, Tao; Qin, Yongxin; Peng, Shang; Wang, Guangtao; Wang, Jinfeng; Gao, Xiang; Huang, Zhiwei; Zhao, Li-Dong
Abstract: PbS has attracted much attention as an excellent thermoelectric material with high development space at middle temperature scope. The thermoelectric performance for n -type PbS was boosted by the cooperative effects of resonance level and Cu dynamic doping in our research. In the first place, In doping improved the electrical transport performance of n -type PbS effectively on account of optimal carrier concentration and resonant level effects, and reduced the lattice thermal conductivity by reason of heightened phonon scattering through impurity atoms scattering simultaneously. Secondly, Cu dynamic doping further increased average power factor to ~18.8 μW cm −1  K −2 at 423 K- 823 K of Pb0.995 In0.005 S+3%Cu owing to higher Seebeck coefficients and suppressed electronic thermal transports at vast temperature span. In result, the best thermoelectric figure of merit ( ZT ) of Pb0.995 In0.005 S+3%Cu at 723 K reached ~1.1 and a record large average ZT ( ZT ave ) of Pb0.995 In0.005 S+3%Cu was achieved ~ 0.8 at 423 K-823 K, which is vital in the implementation of thermoelectric technology. Graphical abstract: Thermoelectric performance of n -type PbS was improved through synergistically integrating In resonant level and Cu dynamic doping. Image 1 Highlights: In boosted PF and decreased κ lat due to resonant level and phonon scattering. Cu suppressed the κ ele effectively and increased average power factor. High average ZT ( ZT ave ) ~ 0.8 of Pb0.995 In0.005 S+3%Cu at 423 K-823 K was achieved.